The need for designing a new Asian family scale - Musa, Ramli (2015)
All available family scales are designed for western countries and there is no validated family scale which is specifically devised for Asian population. The difference in culture and family values warrants the formulation of a specific Asian family scale to cater the regional needs. The intensifying social related problems among children and adolescents are another indication that exploration on family environment is essential. The objectives are to devise and validate a new family scale (English and Malay versions) for Malaysian population. The development of the questionnaire can be divided into 6 stages; identifying the domains of Asian family values, items identification for each domain and language review, pretest the pre-final version, pilot study and validation. Respondents were recruited from different ethnic groups and cultural backgrounds to represent the Malaysian population. They were selected by using stratified quota sampling from various health centers in Malaysia. Total Cronbach’s alpha values on 0.9 with 5 domains were identified by using explanatory factor analysis. From 43 items, 67% had good factor loading (>0.4) and 13 items were finally dropped. The 5 identified domains are namely Togetherness/Harmony (factor 1), Expression (factor 2), Relationship & Family dynamic (factor 3), Conflict (factor 4) and Religiosity & Traditional Practice (factor 5)